2018
DOI: 10.1016/j.bjorl.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Breaking paradigms in severe epistaxis: the importance of looking for the S-point

Abstract: The Stamm's S-point, a novel source of spontaneous severe epistaxis, is reported, and its cauterization was effective and safe. Otolaryngologists must actively seek this site of bleeding in cases of severe epistaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 11 publications
0
35
0
6
Order By: Relevance
“…Ancak şiddetli burun kanaması potansiyel olarak yaşamı tehdit edicidir ve olguların yaklaşık %4'ü hastane yatışını da içeren acil tedavi gerektirmektedir. [9,10] Yaşlı nüfusta daha yaygındır. [11] On yaş altında ve 40 yaş üstünde iki pik yapar.…”
Section: Discussionunclassified
“…Ancak şiddetli burun kanaması potansiyel olarak yaşamı tehdit edicidir ve olguların yaklaşık %4'ü hastane yatışını da içeren acil tedavi gerektirmektedir. [9,10] Yaşlı nüfusta daha yaygındır. [11] On yaş altında ve 40 yaş üstünde iki pik yapar.…”
Section: Discussionunclassified
“…El año 2017, un grupo brasileño, liderado por el Dr. Aldo Stamm, publicó un artículo haciendo referencia a sangrados provenientes de la rama septal de la arteria etmoidal anterior, la cual se ubica en el septum nasal superior, en la proyección de la axila del cornete medio; este punto fue denominado "S point" en honor al autor mencionado 16 . Poco tiempo después, un grupo italiano describió el mismo sitio con una serie de casos 17 .…”
Section: "S-point": Un Sitio a Considerarunclassified
“…Poco tiempo después, un grupo italiano describió el mismo sitio con una serie de casos 17 . Este pedículo vascular arterial, sería origen de epistaxis severa 16 y refractaria en un alto porcentaje de los casos 17 . Una serie de casos reciente con 51 pacientes con epistaxis severa, los cuales se sometieron a evaluación endoscópica sistemática del sitio de sangrado, se reportó que la mitad de los sangrados eran de origen superior, siendo el lugar más frecuente encontrado el "S point", correspondiendo a un 28% del total 2 .…”
Section: "S-point": Un Sitio a Considerarunclassified
“…The adoption of nasal endoscopes in the field of otorhinolaryngology has shifted the paradigm by which epistaxis is treated and has greatly improved outcomes. Endoscopes make it far easier to identify the point of bleeding with a high degree of accuracy [86]. It has been reported that without endoscopic assistance, clinicians fail to identify the point of bleeding in up to 50% of cases involving severe epistaxis [86].…”
Section: Treating Anterior Epistaxismentioning
confidence: 99%